Kaleka Agroforest in Central Kalimantan (Indonesia): Soil Quality, Hydrological Protection of Adjacent Peatlands, and Sustainability - Silvianingsih, Y.A.; Hairiah, K.; Suprayogo, D.; Noordwijk, M. van (MDPI, 2021)
Increased agricultural use of tropical peatlands has negative environmental effects. Drainage leads to landscape-wide degradation and fire risks. Livelihood strategies in peatland ecosystems have traditionally focused on transitions from riverbanks to peatland forests. Riparian ‘Kaleka’ agroforests with more than 100 years of history persist in the peatlands of Central Kalimantan (Indonesia), where large-scale open-field agricultural projects have dramatically failed. Our field study in a Dayak Ngaju village on the Kahayan river in the Pulang Pisau district involved characterizing land uses, surveying vegetation, measuring soil characteristics, and monitoring groundwater during a period of 16 months. We focused on how local practices and farmer knowledge compare with standard soil fertility (physical, chemical, biological) measurements to make meaningful assessments of risks and opportunities for sustainable land use within site-specific constraints. The Kaleka agroforests around a former settlement and sacred historical meaning are species-rich agroforests dominated by local fruit trees and rubber close to the riverbank. They function well with high wet-season groundwater tables (up to −15 cm) compatible with peatland restoration targets. Existing soil quality indices rate the soils, with low soil pH and high Alexch, as having low suitability for most annual crops, but active tree regeneration in Kaleka shows sustainability.